2009
DOI: 10.1007/s00705-009-0515-5
|View full text |Cite
|
Sign up to set email alerts
|

Identification of two RNA silencing suppressors from banana bunchy top virus

Abstract: In order to suppress RNA silencing, many plant and some animal viruses encode RNA silencing suppressors to achieve infection. In this study, we report that B3 and B4, encoded by DNA3 and DNA4 of banana bunchy top virus (BBTV), exhibit RNA silencing suppression activity. B3 and B4 were able to increase the transient expression of green fluorescent protein (GFP) and dramatically enhanced the pathogenicity of potato virus X (PVX) in Nicotiana benthamiana. B4 was able to reverse established gene silencing on an in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
24
2

Year Published

2010
2010
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(26 citation statements)
references
References 52 publications
0
24
2
Order By: Relevance
“…The results of our study contrast with those of Niu et al [57]. They reported that the gene products encoded by DNA 3 (DNA-S; CP) and DNA 4 (DNA-M; MP) of a BBTV isolate from Hainan can suppress RNA silencing, whereas we have shown that DNA-M and DNA-C encoded genes have suppressor activity.…”
Section: Discussioncontrasting
confidence: 86%
See 1 more Smart Citation
“…The results of our study contrast with those of Niu et al [57]. They reported that the gene products encoded by DNA 3 (DNA-S; CP) and DNA 4 (DNA-M; MP) of a BBTV isolate from Hainan can suppress RNA silencing, whereas we have shown that DNA-M and DNA-C encoded genes have suppressor activity.…”
Section: Discussioncontrasting
confidence: 86%
“…One possible reason is that the isolate of BBTV we have examined belongs to the ''South-Pacific'' group [31], whereas the Hainan isolate belongs to the ''Asian'' group [58]. Phylogenetic analyses have shown that these groups of isolates are evolutionarily distinct [57] and upon divergence the two groups may have evolved to use distinct proteins as suppressors of RNA silencing. The predicted amino acid sequences of the Clink from our study and other ''South-Pacific'' BBTV isolates are distinct from those of typical ''Asian'' isolates (Fig.…”
Section: Discussionmentioning
confidence: 92%
“…In addition, we showed that HVT063 could reverse GFP silencing of infiltrated patches but not suppressed systemic gene silencing in newly emerging leaves. Similarly, B3 protein of Banana bunchy top virus also only recovered GFP fluorescence again in the inoculated leaves (39), while PVY HC-Pro could restore the GFP fluorescence of silenced transgenic plants in both old and new leaves and CMV 2b rescues GFP expression only in new emerging leaves (32). A possible clue accounting for this result is that HVT063 may directly interact with the essential components of RNA silencing pathway, which is dosage dependent, or this kind of suppression could not be transferred to remote tissues.…”
Section: Discussionmentioning
confidence: 92%
“…CP-mediated resistance was one of the most common pathogen derived resistance strategies employed against plant viruses and has proven success against many viruses [15]. However CP mediated resistance may only be effective against closely related viruses which share a high level of sequence homology [1,4,19,34,35]. High level of conservation of 96-100 % observed in the CP gene of BBTV isolates of South Pacific group analyzed in the present study suggests that any BBTV CP transgene on the South Pacific isolates likely to provide effective CP mediated resistance against South Pacific BBTV isolates including Sri Lankan isolate.…”
Section: Discussionmentioning
confidence: 99%